Bottom-up nanoarchitectures of semiconductor nano-building blocks obtained via a controllable in situ SEM-FIB thermal soldering method. Issue 34 (21st August 2017) - Zhang, Xuan; Zheng, Xiujun; Zhang, Hong; Zhang, Junli; Fu, Jiecai; Zhang, Qiang; Peng, Chaoyi; Bai, Feiming; Zhang, Xixiang; Peng, Yong
Abstract : Nanoscale semiconductor building blocks can be controllably soldered together via a novel in situ SEM-FIB thermal soldering technique. Abstract : Here we demonstrate that the building blocks of semiconductor WO3 nanowires can be controllably soldered together via a novel nano-soldering technique of in situ SEM-FIB thermal soldering, in which the soldering temperature can be precisely retained in an optimal range to avoid strong thermal diffusion.